Analysis Relates to The Role of Premium Income, Claim Expenses, Investment Result and Risk Based Capital (RBC) Against the General Insurance Companies' Profits Income (Case Study on General Insurance Which Registered in The Indonesia Stock Exchange - Markonah, Markonah (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The research purposes were to analyze the effect of Premium Income, Claim Expenses, Investment Results, Risk Based Capital (RBC) towards Income profits in the General Insurance Industry. Premium Income, Claims Expenses, Investment Returns, and Risk Based Capital (RBC) are often used as independent variables which are thought to have an impact towards company profits that could be measured by ROA as a dependent variable. This research was conducted on general insurance companies that registered on the Indonesia Stock Exchange during the period of 2012 until 2018. The data was obtained through accessing the Indonesia Stock Exchange website. The research sample was selected by Saturated Sampling method where the entire population was included as a sample, so there would be 7 insurance companies that registered on the IDX during that period 2012 - 2018, namely 49 data which were available used in this research. The analytical technique used in this research was multiple regression analysis. And the results from this research indicate that Premium Income had no affect towards profit income, Claim Expenses had no affect towards profit income, Investment Return had a significant positive affect on profits income and Risk Based Capital had a significant positive affect towards General Insurance Companies that registered on the Indonesia Stock Exchange.